(untitled) (Eurasian Scientific Herald, 2025)
We used neurological rating scales to teach patients to self-report pain symptoms in salpingo-oophoritis complicated by chronic pelvic pain syndrome. The results obtained were recommended for the study of clinical symptoms of salpingo-oophoritis complicated by chronic pelvic pain syndrome.